(untitled) (Research, Society and Development, 2020)
The climate of a region can activate precisely the behavior of the population in it, whether in the characteristics of clothing or in the activities carried out on a daily basis. This also occurs with buildings, which the climate brings over them, makes it necessary to adapt them to the local reality, since such adjustments are crucial for the good quality of life of its inhabitants. Thus, this work aims to present the degree of satisfaction of information of the population of the Social Housing Garden of Eden, located in the district of Morada Nova, in the municipality of Marabá/PA. For this, a research based on the application of a questionnaire, directly linked to the theme, covering several aspects related to the thermal perception of the user, with responses to ’satisfied’ or ’dissatisfied’ thermally. The research pointed out the thermal dissatisfaction of the residents, exposing the need for solutions that adapt the thermal environment to the reality experienced in the place, and consequently, that improves the quality of life of its inhabitants.